2016
DOI: 10.11621/pir.2016.0209
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study of the influence of a communicator’s speech characteristics on a recipient’s willingness to maintain interaction in cross-cultural online communication

Abstract: The success of cross-cultural online communication in an academic environment is defined by the degree of student involvement in such an interaction. The authors' experience testifies that a number of objective, language, and psychological factors may decrease the activeness of these interactions, and as a result learning may not be effective for students in these types of cross-cultural interactions. Among such factors the current article investigates the influence of a communicator's speech peculiarities on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Lázár () also suggested that students generally perceive that developing a relationship with their partner is challenging, especially when different cultural conceptions cause significant mistakes in intercultural communication. Rudenko and Krylova () concluded that students' repetitive speech “mistakes” decreases their subsequent willingness to communicate with their foreign partners. In a similar vein, Ke () reported that some students find it too difficult to develop a positive and stable linguistic identity.…”
Section: Introductionmentioning
confidence: 99%
“…Lázár () also suggested that students generally perceive that developing a relationship with their partner is challenging, especially when different cultural conceptions cause significant mistakes in intercultural communication. Rudenko and Krylova () concluded that students' repetitive speech “mistakes” decreases their subsequent willingness to communicate with their foreign partners. In a similar vein, Ke () reported that some students find it too difficult to develop a positive and stable linguistic identity.…”
Section: Introductionmentioning
confidence: 99%